Inquérito sorológico da neosporose bovina no estado de Mato Grosso, Centro-Oeste, Brasil - Costa, Jackeliny dos Santos (2018)
The protozoan Neospora caninum is an obligate intracellular parasite and etiological agent of neosporosis, one of the most widespread and frequent causes of abortion in cattle worldwide. To estimate the prevalence of anti-N. caninum antibodies and the risk factors associated with the disease in the state of Mato Grosso, Brazil, serum samples of 7800 cows aged 24 months or more from 793 herds collected between September and December 2014 were submitted to the Indirect Immunofluorescence Assay (IFA) using a cutoff point of 1:100. An epidemiological questionnaire was applied to each sampled farm. The prevalence found in the animals and herds sampled was 19.27% (95% CI, 16.51%, 22.04%) and 66.58% (95% CI, 63.3%, 69.9%), respectively. Logistic regression indicated that the following variables were positively associated with the probability of an animal being positive in a herd: presence of dogs, presence of equines and veterinary assistance; and three were negatively associated factors: no occurrence of abortion, breed (zebu) and breed (European). A spatial analysis indicated that the relative risk of the disease is not spatially constant, indicating a higher risk for the south of the state, showed that farms of high prevalence are close to each other and those of low prevalence are also close to each other.